The beneficial effect of intra-articular injection of losartan on the microfracture mediated cartilage repair is dose dependent. Issue 7 (30th July 2021) - Gao, Xueqin; Utsunomiya, Hajime; Scibetta, Alex; Ravuri, Sudheer; Ruzbarsky, Joseph; Talwar, Camille; Arner, Justin; Lowe, Walter; Philippon, Marc; Huard, Johnny; Logan, Catherine
Objectives: 1. To determine the dosage and beneficial effects of intra-articular injection of losartan on microfracture-mediated cartilage repair and normal cartilage homeostasis. Methods: Rabbits were divided into 5 groups (n=6):a microfracture group (MFX) and 4 different losartan treatment cohorts received varying dosages of IA losartan (0.1, 1, 10 and 100 mg/knee). An osteochondral defect (5mm) was created in the trochlear groove cartilage and 5 microfracture perforations were performed in the osteochondral defect. Both injured and contralateral knee joints were injected with losartan IA at days 0, 14 and 28 after surgery. Rabbits were sacrificed at 6 weeks after surgery for analysis including gross observation, micro computed tomography, histology analysis and reverse transcription quantitative PCR. Results: Micro computed tomography analysis and gross observation demonstrated comparable subchondral bone healing andhyaline-like appearing cartilage morphology in the 0.1, 1 and 10mg/knee losartan IA injection groups relative to the MFX group. Conversely, IA injection of losartan at 100mg/knee dosage showed neither bony defect healing nor cartilage repair. Histology revealed higher O'Driscoll scores and hyaline cartilage regeneration in the 1mg/knee cohort when compared to the MFX group. In contrast, 100mg/knee losartan showed the lowest histology score and no cartilage repair. IA injection of losartan at the doses of 0.1, 1 and 10mg/knee did not cause adverse effects on uninjured cartilage while 100mg/knee dose induced cartilage damage. Q-PCR results showed down-regulation of the TGFβ signaling pathway after losartan injection. Conclusions: Intra-articular injection of losartan at the dose 1mg/knee was most effective for enhancement of microfracture-mediated cartilage repair without adversely affecting uninjured cartilage. Conversely, high dose (100mg/knee) IA injection of losartan inhibited cartilage repair in osteochondral defect and was chondrotoxic to normal articular cartilage.